1000-7
993-7
986-7
979- 7
972-7
965-7
958-7
951-7
944-7
937-7
930-7
923-7
916-7
909-7
902-7
895-7
888-7
881-7
874-7
867-7
860-7
853-7
846-7
839-7
832-7
825-7
818-7
811-7
804-7
797-7
790-7
783-7
776-7
769-7
762-7
755-7
748-7
741-7
734-7
727-7
720-7
713-7
706-7
699-7
692-7
685-7
678-7
671-7
664-7
657-7
650-7
643-7
636-7
629-7
622-7
615-7
608-7
601-7
594-7
587-7
580-7
573-7
566-7
559-7
552-7
545-7
538-7
531-7
524-7
517-7
510-7
503-7
496-7
489-7
482-7
475-7
468-7
461-7
454-7
447-7
440-7
433-7
426-7
419-7
412-7
405-7
398-7
391-7
384-7
377-7
370-7
363-7
356-7
349-7
342-7
335-7
328-7
321-7
314-7
307-7
300-7
293-7
286-7
279-7
272-7
265-7
258-7
251-7
244-7
237-7
230-7
223-7
216-7
209-7
202-7
195-7
188-7
181-7
174-7
167-7
160-7
153-7
146-7
139-7
132-7
125-7
118-7
111-7
104-7
97-7
90-7
83-7
76-7
69-7
62-7
55-7
48-7
41-7
34-7
27-7
20-7
13-7
6-7
-1
Решение.
15. (b + c)(b - c) - b(b - 2c) = b^2 - c^2 - b^2 + 2bc = -c^2 + 2bc
16. (a - c)(a + c) - c(3a - c) = a^2 - c^2 - 3ac + c^2 = a^2 - 3ac
17. a(a + 5b) - (a + b)(a - b) = a^2 + 5ab - (a^2-b^2) = a^2 + 5ab - a^2 + b^2 = 5ab + b^2
18. b(3a - b) - (a - b)(a + b) = 3ab - b^2 - (a^2-b^2) = 3ab - b^2 - a^2 + b^2 = 3ab - a^2
19. (y + 10)(y - 2) - 4y(2 - 3y) = y^2 - 2y + 10y - 20 - 8y + 12y^2 = 13y^2 - 20
20. (a - 4)(a + 9) - 5a(1 - 2a) = a^2 + 9a - 4a - 36 - 5a + 10a^2 = 11a^2 - 36
21. (2b - 3)(3b +2) - 3b(2b+3) = 6b^2 + 4b - 9b - 6 - 6b^2 - 9b = -14b - 6
22. (3a - 1)(2a - 3) - 2a(3a + 5) = 6a^2 - 9a - 2a + 3 - 6a^2 - 10a = -21a + 3
23. (m + 3)^2 - (m - 2)(m + 2) = m^2 + 6m + 9 - (m^2 - 4) = m^2 + 6m + 9 - m^2 +4 = 6m + 13
24. (a - 1)^2 - (a + 1)(a - 2) = a^2 - 2a + 1 - (a^2 - 2a + a - 2) = a^2 - 2a + 1 - a^2 + a + 2 = -a + 3
25. (c + 2)(c - 3) - (c - 1)^2 = c^2 - 3c + 2c - 6 - (c^2 - 2c + 1) = c^2 - 3c + 2c - 6 - c^2 + 2c - 1 = c - 7
26. (y - 4)(y + 4) - (y - 3)^2 = y^2 - 16 - (y^2 - 6y + 9) = y^2 - 16 - y^2 + 6y - 9 = -25 + 6y
27. (a - 2)(a + 4) - (a + 1)^2 = a^2 + 4a - 2a - 8 - (a^2 +2a + 1) = a^2 + 4a - 2a - 8 - a^2 - 2a - 1 = -9
28. (b - 4)(b + 2) - (b - 1)^2 = b^2 + 2b - 4b - 8 - (b^2 - 2b + 1) = b^2 + 2b - 4b - 8 - b^2 + 2b - 1 = 0 - 9 = -9
42:7=6кг-хек и окунь в день
6:2=3кг хека или окуня